2014
DOI: 10.1084/jem.20131831
|View full text |Cite
|
Sign up to set email alerts
|

The BTB-ZF transcription factor Zbtb20 is driven by Irf4 to promote plasma cell differentiation and longevity

Abstract: Zbtb20 facilitates terminal differentiation of B cells into antibody-secreting cells, and its expression is dependent on Irf4 and independent of Blimp1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 60 publications
4
99
0
Order By: Relevance
“…During this phase of activation, the B cells continue to maintain expression of CXCR5; the balance between CXCL13 expression in the follicles and CCL19/21 expression in the T cell zone positions B cells at the border of the T cell zone [17]. Meanwhile, naive T cells in the T cell zone encounter their cognate antigen, here presented by DCs, initiating commitment towards a T follicular helper (Tfh) cell phenotype [19]. Tfh cell commitment is accompanied by CCR7 down-regulation and CXCR5 upregulation, promoting Tfh cell migration to the T/B cell boundary where they can support B cell expansion [20,21].…”
Section: Gc Structure Formation and B Cell Movementmentioning
confidence: 99%
“…During this phase of activation, the B cells continue to maintain expression of CXCR5; the balance between CXCL13 expression in the follicles and CCL19/21 expression in the T cell zone positions B cells at the border of the T cell zone [17]. Meanwhile, naive T cells in the T cell zone encounter their cognate antigen, here presented by DCs, initiating commitment towards a T follicular helper (Tfh) cell phenotype [19]. Tfh cell commitment is accompanied by CCR7 down-regulation and CXCR5 upregulation, promoting Tfh cell migration to the T/B cell boundary where they can support B cell expansion [20,21].…”
Section: Gc Structure Formation and B Cell Movementmentioning
confidence: 99%
“…Interestingly, IRF4 binds to the Zbtb20 promoter and up-regulates Zbtb20 expression (37,38). Thus, LMP2A-and IRF4-mediated up-regulation of Zbtb20 may be an important mechanism by which EBV promotes plasma cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, LMP2A-and IRF4-mediated up-regulation of Zbtb20 may be an important mechanism by which EBV promotes plasma cell survival. Recent studies revealed that Zbtb20, which is a Bcl6 homolog and a member of the broad complex BTB zinc finger family, is a transcriptional repressor that has critical roles in plasma cell differentiation and survival (37,45). Zbtb20 is physiologically expressed in B1 and GC B cells, with highest expression in long-lived bone marrow ASCs (37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations